Clinical Remission of Chronic Refractory Pelvic Symptoms in Three Men - Bradley R. Hennenfent; Antonio Espinosa Feliciano (The Scientific World Journal)
We report on three American men with chronic refractory pelvic pain, urinary symptoms, and sexual dysfunction who traveled to the Philippines for treatment. In the Manila Genitourinary Clinic, the patients were treated with microbial diagnosis, antimicrobial therapy, and 19, 27, and 21 prostatic massages respectively. All three patients underwent resolution of symptoms.